A study of how ciliates detect their predators through chemoreception sensors - Ashvin Ravichandran (Nanyang Technological University, 2022)
Chemoreception is one of an integral mechanism that benefits the ciliates to a great extent. The ciliates uses chemoreception as a means to detect any incoming predators such as dinoflagellates in its environment that may be a threat to the ciliates. When it is deemed as a threat to them, it allows them to swim away and escape from their predators easily. The objective of this study is to model how chemoreception is being carried out by the ciliates in the aquatic environment. This model was developed using ANSYS simulation 2021 R2 software. From this model, I will be able to understand and see how chemoreception works visually. With the model results generated, I will have to make sure that my simulation matches how a chemical diffuses in the water. If the simulation has a similar characteristic with how diffusion occurs in an aquatic environment, then my model is deemed to be a realistic chemoreception model. In order for me to have a realistic model, I will have to do some computations of the size and velocity of the particle to input into my chemoreception setup. If I do not get a realistic model, I will do some amendments with the calculated values in order to achieve a realistic simulation. This study also covers literature review on ciliates morphology, dinoflagellate morphology, interaction of predator and prey during capture and the process of chemoreception. With the literature review on these topics, I was able to understand how important chemoreception is for the ciliates. Without chemoreception, ciliates will not be able to sense any predators nearby which is a huge disadvantage the ciliate family. Since ciliates are a vital part to the marine ecosystem, chemoreception does help the population of ciliates to thrive better.